Throughput optimization for wireless OFDM system in downlink transmission using adaptive techniques - Youssef Fakhri; Benayad Nsiri; Driss Aboutajdine; Josep Vidal (2006 International Conference on Wireless Communications, Networking and Mobile Computing, 2006)
In this paper we present a mathematical technique for determining the optimum transmission rate and packet size in wireless system that have multi-carriers for OFDM modulation in downlink transmission. The throughput is defined as the number of bits per second correctly received. Trade-offs between the throughput and the operation range are observed, and equations are derived for the optimal choice of the design variables. These parameters are SNR dependent and can be adapted dynamically in response to the mobility of a wireless data terminal. We also look at the joint optimization problem involving all the design parameters together. We find, however, that not all of the three parameters (b,SNR,L) need to be adapted simultaneously: in the low SNR region it is achieved by adapting the symbol rate so that the received SNR per symbol stays at some preferred value. Finally, we give a characterization of the optimal parameter values as functions of received SNR